Menumbuhkan Minat Literasi Generasi Menghadapi Tantangan Zaman Dalam Perspektif Al-Qur’an - Siti Hizliah (Syntax Idea, 2022)
The millennial generation is a modern generation that has one of the characteristics of a consumptive lifestyle. Apart from the consumptive lifestyle of the millennial generation, it is also a technology-based life. The purpose of the research conducted is to foster a high interest in reading in facing the challenges of modern life. The research method used isthe analysis method. Research methods used in solving problems include analytical methods. The image caption is placed as part of the image title (figure caption) instead of being part of the image. The methods used in completing the study are written in this section. The results and discussions of the millennial generation are a social construction in which there is a group of people who have the same age and experience the same history. Individuals who belong to a generation, are those who have the same year of birth in a span of 20 years and are in the same social dimension and historical dimension. Conclusion In the process of educating and fostering children is inseparable from various efforts and efforts, of course we as parents and educators will always provide the best education.